Comparative Analysis of Behavioral Theories in Promoting CPR: A Theory-Based Approach to Cardiopulmonary Resuscitation Training in Community - Abdurahman Wahid; Dina Septiany; Sri Widati; Sri Haryuni; Nurma Afiani; Novita Ana Anggraini (Jurnal Penelitian Pendidikan IPA, 2025)
Sudden cardiac arrest (SCA) is a critical emergency that need immediate intervention to prevent death. This review will discuss behavioral theories relevant to the promotion of Cardiopulmonary Resuscitation in the community. Findings from previous studies were analyzed using approaches from three theories, namely the Integrated Behavior Model (IBM), Health Belief Model (HBM), and Social Cognitive Theory (SCT). This narrative review examines three behaviour theories applicability as a conceptual model for CPR promotion, focusing on enhancing community engagement and response rates to out-of-hospital cardiac arrests (OHCA). Articles search keywords used for review including "CPR Intention Factors," "Willingness to Perform CPR," "Predictors of CPR Intention," and "Social Determinants of CPR.". Database used were ProQuest, ScienceDirect, and Sage Journals. Eleven articles were utilized, revealing findings that experience, skills, demographic factors, culture, training, attitudes, norms, and knowledge contribute to community CPR actions. Findings suggest that IBM can effectively support CPR promotion strategies, fostering a culture of preparedness and resilience against cardiac emergencies.